2005
DOI: 10.1016/j.jtcvs.2004.07.056
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surgical case volume on outcome after the Norwood procedure

Abstract: Survival after the Norwood procedure is associated with institutional Norwood procedure volume but not with individual surgeon case volume, suggesting the need for improvements in institutional-based approaches to the care of children with hypoplastic left heart syndrome and the need for establishing regional referral centers for such high-risk procedures to improve patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 19 publications
3
88
1
1
Order By: Relevance
“…Using data from hospital members of the Child Health Corporation of America, Checchia PA et al 14 studied 1105 newborns from 1988 to 2001 admitted with the diagnosis of HLHS, and observed that 801 had undergone the Norwood procedure, 39 heart transplantation, and the remaining 265 (24%) did not undergo surgical intervention. …”
Section: Resultsmentioning
confidence: 99%
“…Using data from hospital members of the Child Health Corporation of America, Checchia PA et al 14 studied 1105 newborns from 1988 to 2001 admitted with the diagnosis of HLHS, and observed that 801 had undergone the Norwood procedure, 39 heart transplantation, and the remaining 265 (24%) did not undergo surgical intervention. …”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, research has shown an association between low case volume and poor outcomes in a multitude of surgical procedures, [1][2][3][4][5] such as hysterectomy, 6 pancreatectomy, 5,7 esophagectomy, 5 pelvic exenteration, 5 and coronary artery bypass surgery. 2,8,9 Studies have also shown this relationship in several pediatric procedures of varying complexity, such as cardiac surgery, 10,11 pyloromyotomy, 12 appendectomy, 13,14 and inguinal hernia repairs. 13,14 In the field of transplantation, a landmark manuscript published in 1999 suggested that programs performing ,20 transplants per year had inferior outcomes.…”
Section: What This Study Addsmentioning
confidence: 90%
“…Pediatrics 2012;129:e370-e376 Several previous studies have documented a relationship between center volume and outcome in children undergoing a variety of surgical procedures including liver transplant, appendectomy, pyloromyotomy, and heart surgery. [1][2][3][4][5][6][7][8][9][10] In children undergoing heart surgery, it has been shown that higher surgical volume is associated with improved survival, particularly for high risk surgeries. 1 However, there are limited data regarding factors that may mediate this volume-outcome relationship, and may thus be targeted for quality improvement.…”
Section: Methodsmentioning
confidence: 99%